2008
DOI: 10.1590/s0100-204x2008000800005
|View full text |Cite
|
Sign up to set email alerts
|

Perfilhamento e produtividade de cana-de-açúcar com diferentes alturas de corte e épocas de colheita

Abstract: O objetivo deste trabalho foi avaliar a relação entre a altura do corte basal de colmos e da época de colheita da cana-de-açúcar e suas conseqüências no perfilhamento e na produtividade da cana-soca. O delineamento experimental foi o de blocos ao acaso, em fatorial 2x3x3, constituídos de dois genótipos (IAC86-2480 e RB72454), três alturas de corte (0, 10 e 20 cm, acima do nível do solo) e três épocas de colheita (maio, julho e setembro de 2006), com quatro repetições, em Jaú, SP. O 'IAC86-2480' mostrou maior n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
27

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 6 publications
3
14
0
27
Order By: Relevance
“…Just as for cane-plant, the higher sugar yield was a result of the greater stalk productivity. Similar results were observed by Silva et al (2008), who observed no negative effects on the technical quality of ratoon stalks induced by applications of 5.32 and 10.65 t ha -1 sludge.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Just as for cane-plant, the higher sugar yield was a result of the greater stalk productivity. Similar results were observed by Silva et al (2008), who observed no negative effects on the technical quality of ratoon stalks induced by applications of 5.32 and 10.65 t ha -1 sludge.…”
Section: Resultssupporting
confidence: 89%
“…A higher yield was reported by Maule et al (2001) who obtained 154 t ha -1 , cultivating the same variety for 18 months in Red-Yellow Argisol (Hapludult). This is to be expected, because cane grown for 12 months is less productive than when grown for 18 months (Silva et al, 2008). Therefore, the yields of cane-plant grown for 12 months in this study can be considered excellent, particularly in the treatments with 7.2 and 10.8 t ha -1 sludge.…”
Section: Resultsmentioning
confidence: 66%
“…1137, 2011 desenvolvimento da planta, mesmo sob condições ambientais adversas (CASILLAS et al, 1986 As colheitas anuais e rebrotas fazem com que a cana-de-açúcar seja considerada semi-perene. A cada ciclo de colheita dos colmos tem início a brotação da soca, e um novo processo de perfilhamento é estabelecido (RODRIGUES, 1995;SILVA et al, 2008 …”
Section: Uso De Biostimulantes Na Cana-de-açúcarunclassified
“…La reserva energética acumulada en la base de los tallos, por la altura del corte, favorece el rebrote de la caña de azúcar. La época de cosecha interfiere en la productividad de los tallos y de azúcar (Silva et al, 2008).…”
Section: Introductionunclassified